Penerapan Model Pembelajaran Connecting Organizing Reflecting Extending untuk Meningkatkan Pemahaman Konsep Matematis Peserta Didik Kelas VIII SMP Negeri 19 Padang - BUNGA OKTARI ALDI (Jurnal Edukasi dan Penelitian Matematika, 2019)
Understanding  the  concept  is  a  basic  ability  that  must  be  possessed  by  every  student.  But  in reality learning is still centered on the teacher, the teacher actively provides information to students, while students are still passive in learning. So that, it results in understanding of concepts and learning activities of  low  students.  One  of  the  efforts  made  to  improve  students'  understanding  of  concepts  is  to  apply  the Connecting  Organizing  Reflecting  Extending  (CORE)  learning  model.  The  purpose  of  this  study  is  to describe whether understanding mathematical concepts of students who learn by learning CORE is better than understanding mathematical concepts of students who learn by direct learning.Based on the results of the data analysis, it was concluded that understanding mathematical concepts of students who learn using the CORE learning model is better than understanding concepts of students who learn by direct learning. Likewise the learning activities of students also increased after the CORE learning model was applied. Keyword  –  Understanding  of  mathematical  concepts,  the  Connecting  Organizing  Reflecting  Extending